"Beyond Jesus": faith in resurrection and the emerging christology - Zúñiga Valerio , Hanzel J. (2025)
The research of the “historical Jesus” or the modern and plausible reconstruction of Jesus the Galilean does not look for the divinization of the character with the relevance that it searches for other historical facts about the origin of Christianity. This “construction process” of the divinity was dynamic and developed in the next two decades of Jesus’s death in order to be grounded 3 centuries after the dogmatic proclamations of the religious councils. However, the main argument of this research was attended following the theological new lecture of Jesus’s death made by his followers plus social and psychological elements of the “resurrection” metaphor.